Community Product from Rubber Processing Materials in Phipun District, Nakhon Si Thammarat Province - Chanmuang, Napaphach; Rattanapan, Chatchawan; Saetiaw, Paemika (Area Based Development Research Journal, 2018)
This research investigates issues regarding community’s product development of rubber materials in relation to customer needs. In particular, it studies the current states of problems, the needs for product development, and the development process of new products from rubber materials. The focal point is on community involvement throughout the entire process, namely, planning and directing, designing, and producing. The study employs a combination of qualitative and quantitative research methods. An operational model is used to find patterns and techniques in the production of processed rubber products. The process used in the study is divided into 3 steps: 1) exploring the problem and the needs to develop a community product model, 2) searching for new methods to improve the product potentiality and design, and 3) transferring the acquired knowledge. The samples of producers are entrepreneurs from the OTOP (One Tambon One Product) Creamy Pu Rubber Products from Phipun district, Nakhon Si Thammarat province while the customer samples are 100 people in Nakhon Si Thammarat province. The research finds that entrepreneurs lack knowledge for product development and have some production process problems. The improvement of the products such as key rings, backrest cushions, and shoulder bags makes use of graphic decorative patterns derived from a design of overlapping lotus lobes, the idea inspired by the popular tradition of Loy Krathong. The findings show that people in the community have learned the product design and development processes. At the same time, this communal involvement in the entire planning and developing stages through the product salability gives the community a sense of pride.